Intensi Kewirausahaan Mahasiswa: Theory of Planned Behaviour Approach - Yunita Eriyanti Pakpahan; Christnova Hasugian; Eduard Eduard; Supri Supri (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The COVID-19 pandemic brings new challenges and threats for fresh graduates, namely the reduced number of jobs available for new graduates. Therefore, the solution that is expected to solve this problem is the students must dare to be entrepreneurs by utilizing current technology. The purpose of this research is to analyze and examine the effect of entrepreneurial education, innovation, and relation support on entrepreneurial intention. It is an associative-causal research. The population in this research was students in Universitas Quality Berastagi and Universitas Quality Medan, accounting and management study program consisted of 178 students. The data were collected by using questionnaire. The sampling method used in this research was all population became the sample of the research. The hypotheses were tested by using the linear regression analysis. The result of this research showed that, simultaneously and partial, entrepreneurial education, innovation, and relation support had some effect on entrepreneurial intention.